Volumetric modulated arc therapy planning for primary prostate cancer with selective intraprostatic boost determined by (18)F-choline PET/CT - Kuang, Yu (Int J Radiat Oncol Biol Phys, 2015)
OBJECTIVE: Evaluate expected tumor control and normal tissue toxicity for prostate volumetric modulated arc therapy (VMAT) with and without radiation boost to an intraprostatic dominant lesion (IDL) defined by (18)F-fluorocholine PET/CT. METHODS: Thirty patients with localized prostate cancer underwent (18)F-fluorocholine PET/CT before treatment. Two VMAT plans, plan(79Gy) and plan(100-105Gy), were compared for each patient. The whole-prostate planning target volume (PTV(prostate)) was prescribed 79 Gy in both plans, however plan(100-105Gy) added simultaneous boost doses of 100 Gy and 105 Gy prescribed to IDLs defined by 60% and 70% of maximum prostatic uptake on (18)F-fluorocholine PET (IDLsuv60% and IDLsuv70%, respectively, with IDLsuv70% nested inside IDLsuv60% to potentially enhance tumor specificity of the maximum point dose). Plan evaluations included histopathologic correspondence, isodose distributions, dose-volume histograms, tumor control probability (TCP), and normal tissue complication probability (NTCP). RESULTS: Planning objectives and dose constraints proved feasible in 30/30 cases. Prostate sextant histopathology was available from 28 cases, confirming that IDL(suv60%) adequately covered all tumor-bearing prostate sextants in 27 cases and provided partial coverage in one case. Plan(100-105Gy) had significantly higher TCP than Plan(79Gy) across all prostate regions for α/β ratios ranging from 1.5 Gy to 10Gy (p < 0.001 each case). There were no significant differences in bladder and femoral head NTCP between plans, and slightly lower rectal NTCP (endpoint: grade 2+ late toxicity or rectal bleeding) for plan(100-105Gy). CONCLUSION: VMAT can potentially increase the likelihood of tumor control in primary prostate cancer while observing normal tissue tolerances through simultaneous delivery of a steep radiation boost to an (18)F-fluorocholine PET-defined IDL.